Gastrotomy for Removal of an Expanding Polyurethane Foam Foreign Body Following a Suicide Attempt: A Case Report - Leal Contini Sanches, João Gabriel; Aires, Natália de Oliveira; Sanches, Bruna Julio; Petillo, Rosana (Brazilian Journal of Case Reports, 2026)
Suicide attempts represent a major public health concern in Brazil, with a wide variety of methods employed. Early recognition and prompt management of complications are essential to reduce morbidity and mortality. We describe the case of a patient who presented with hematochezia and abdominal pain after ingesting expanding polyurethane foam. Initial imaging studies demonstrated gastric wall thickening. Upper gastrointestinal endoscopy revealed a large intragastric foreign body, and the patient subsequently underwent gastrotomy for surgical removal of the foreign body, followed by ulcer repair secondary to the gastric lesion. The postoperative course was uneventful, with progressive clinical improvement. The patient was subsequently managed for both medical and psychiatric conditions and was discharged after recovery. This case highlights the clinical consequences of expanding polyurethane foam ingestion, the associated gastrointestinal complications, and the surgical management required in this uncommon presentation.